8x-12+7=-3

Simple and best practice solution for 8x-12+7=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-12+7=-3 equation:


Simplifying
8x + -12 + 7 = -3

Reorder the terms:
-12 + 7 + 8x = -3

Combine like terms: -12 + 7 = -5
-5 + 8x = -3

Solving
-5 + 8x = -3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 8x = -3 + 5

Combine like terms: -5 + 5 = 0
0 + 8x = -3 + 5
8x = -3 + 5

Combine like terms: -3 + 5 = 2
8x = 2

Divide each side by '8'.
x = 0.25

Simplifying
x = 0.25

See similar equations:

| 3x^2+30x-4=0 | | 4x+11=10x-7 | | z+5=-5 | | 4(3x-5)+x=z | | 11y-12=6y+8 | | 6y+4=2y+20 | | 5xa+7=c+a | | 4(3x-5)+x= | | 10x+5(z-12)=0 | | -3x-10=-2x+4 | | 0.6(j-2)=0.3l | | 20+x=2(20-2x) | | 14-d=45 | | x+2x+2x-30=5400 | | 8-n-3n=6 | | -6x+2y=5 | | 6x-2(-6x+3)=120 | | 2x+20=-3x+50 | | 4(x-3)+7=-3 | | 7x+2(3x+7)=144 | | 6x^2+9x-4=38 | | ax^3+bx-5=0 | | D+8=-7 | | -4(n-b)=12 | | 9(n+6)-5(2+2n)=-8n+5n | | 5(x+4)+14=59 | | 21=3(c-9) | | 6x-2(-6+3)=120 | | 3a+3b+3c=3b | | 7x-2-3x=-10 | | x+3.6=0.5 | | 2(8+4*2)= |

Equations solver categories